Development of Soft Computing-based Predictive Tools for Estimating the Young Modulus of Weak Rocks - Köken, Ekin; Strzałkowski, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The deformation characteristics of rocks are of vital importance in addressing most geomechanical issues as they are one of the most critical input parameters in rock engineering analyses. For this reason, robust forecasting models are required when analysing the stability of tunnels, slopes, mine galleries, and other underground excavations. In this research, novel predictive models are proposed to estimate the tangential Young modulus (Eti) of weak rocks.
Keywords: weak rocks; soft computing; mathematical modelling; deformation modulus